Decoupling of quark condensate from the effective nucleon mass at high density (ϱ) and temperature (T) - Delfino, A; Dey, Jishnu; Dey, Mira; Malheiro, M (Elsevier, 1995)
It is found that the quark condensate 〈qq〉, instead of decreasing at high ρ{variant}, as commonly expected, starts to increase after a certain density (∼ 1.5ρ{variant}0 - in standard relativistic nuclear matter models. However, when the models contain coupling constants which are density dependent, 〈qq〉 → 0 at high ρ{variant} and T, and in addition, the effective nucleon mass changes little, showing a decoupling of the mass from the condensate. © 1995.
Keywords: Chiral symmetry restoration; Effective pion-nucleon sigma term; Finite temperature at zero density; Linear Walecka model; Mean field theory; Nuclear matter; Quark condensate; Zimanyi-Moszkowski models